Scrambler therapy: what's new after 15 years? The results from 219 patients treated for chronic pain. Issue 2 (January 2019) - Ricci, Marianna; Fabbri, Laura; Pirotti, Sara; Ruffilli, Nicola; Foca, Flavia; Maltoni, Marco
Abstract : Abstract: Chronic pain is often difficult to treat, requiring a comprehensive multidisciplinary therapeutic intervention and a high level of management expertise. This is particularly true for patients who are unresponsive to standard treatments for chronic pain, for which Scrambler Therapy (ST) is indicated. The aim of the present study was to evaluate the impact of ST on patient-reported moderate to severe chronic pain. This was a prospective trial on 219 patients affected by chronic pain from April 2010 to March 2016. The study consisted of 2 consecutive weeks of treatment with ST (one 30-min daily session, 5 days a week) (T0, T1, T2) and a 2-week follow-up (T3, T4). Patients were asked to describe the pain using the Numeric Rating Scale (NRS) immediately prior to and after the treatment. Two hundred nineteen patients were treated for chronic pain of different nature with mean values of 6.44 (± 2.11) at T0, 3.22 (± 2.20) at T2, and 3.19 (± 2.34) at T4. A reduction in the symptomatology from T0 to T2 was maintained throughout T4 ( P value < .0001). Of the 219 patients treated with ST, 83 (37.9%) had cancer pain and 136 (62.1%) had non-cancer pain. No adverse events were reported. Future research should focus on individual response, retreatment, and maintenance therapy. The data showed a statistically significant impact of ST, which was maintained during follow-up, on patients suffering from chronic pain of different nature.